Jia, Ruixue and Hongbin Li. The Highest Exam: How the Gaokao Shapes China - Malamud, Ofer (Journal of Economic Literature, 2026)
Ofer Melamud of Northwestern University reviews “The Highest Exam: How the Gaokao Shapes China” by Ruixue Jia and Hongbin Li. The Econlit abstract of this book begins: “Describes the structure of China's education system as a centralized hierarchical tournament, focusing on how this system influences China's institutions and social life.”